Beyond Conceptual Knowledge: The Impact of Children’s Theory-of-Mind on Dyadic Spatial Tasks - Viana, Karine M. P.; Zambrana, Imac M.; Karevold, Evalill B.; Pons, Francisco (Frontiers in Psychology, 2016)
Recent studies show that Theory of Mind (ToM) has implications for children’s social competences and psychological well-being. Nevertheless, although it is well documented that children overall take advantage when they have to resolve cognitive problems together with a partner, whether individual difference in ToM is one of the mechanisms that could explain cognitive performances produced in social interaction has received little attention. This study examines to what extent ToM explains children’s spatial performances in a dyadic situation. The sample includes 66 boys and girls between the ages of 5-9 years, who were tested for their ToM and for their competence to resolve a Spatial task involving mental rotation and spatial perspective taking, first individually and then in a dyadic condition. Results showed, in accordance with previous research, that children performed better on the Spatial task when they resolved it with a partner. Specifically, children’s ToM was a better predictor of their spatial performances in the dyadic condition than their age, gender and spatial performances in the individual setting. The findings are discussed in terms of the relation between having a conceptual understanding of the mind and the practical implications of this knowledge for cognitive performances in social interaction regarding mental rotation and spatial perspective taking.